The Value of Fecal Markers in Predicting Relapse in Inflammatory Bowel Diseases - Galgut, Bianca J.; Lemberg, Daniel A.; Day, Andrew S.; Leach, Steven T. (Frontiers in Pediatrics, 2018)
The Inflammatory Bowel Diseases (IBD) are lifelong chronic illnesses that place an immense burden on patients. The primary aim of therapy is to reduce disease burden and prevent relapse. However, the occurrence of relapses is often unpredictable. Current disease monitoring is primarily by way of clinical indices, with relapses often only recognised once the inflammatory episode is established with subsequent symptoms and gut damage. The window between initial up-regulation of the inflammatory response and the recognition of symptoms may provide an opportunity to prevent the relapse and associated morbidity. This review will describe the existing literature surrounding endoscopy and biomarkers in serum and stool and their value as predictive indicators of relapse of Inflammatory Bowel Disease. Fecal biomarkers offer promise as a convenient, non-invasive, low cost option for disease monitoring that is predictive of subsequent relapse. To exploit the potential of fecal biomarkers in this role, further research is now required. This research needs to assess multiple fecal markers in context with demographics, disease phenotype, genetics and intestinal microbiome composition, to build disease behaviour models that can provide the clinician with sufficient confidence to intervene and change the long-term disease course.